Simulation of Modified TRIGA-2000 with Plate-Type Fuel under LOFA Using EUREKA2/RR-Code - S. Dibyo; K.S. Sudjatmi; S Sihana; Ign.D. Irianto (PPIKSN-BATAN, 2018)
The TRIGA-2000 research reactor in Bandung, Indonesia, has operated for over 50 years. Recently, the problem of fuel availability arises, since its fuel is no longer produced. A modification of reactor core with new plate-type fuel has been suggested. The study of the neutronic assessment of plate-type fuel elements reactor core had been done. The next assessment that needed to be done was thermal-hydraulic analysis. The purpose of this study is to simulate the thermal-hydraulic characteristics of major parameters, such as reactor power, fuel cladding temperature, and departure from nucleate boiling ratio (DNBR) due to LOFA transient, using EUREKA2/RR code. During steady-state condition, downward flow forced convection mode for core coolant system is operated. The upward flow occurs when the natural circulation mode takes place. Hottest core channels temperature during LOFA conditions was considered. The reactor core was modeled as three channels, i.e., the hottest channel, the average channel, and the channel for control assemblies, respectively. The simulation was based on the steady-state condition of 2 MWt reactor power, cooling mass flow rate of 63.5 kg/s,and inlet coolant temperature to the core of35.5°C. The result shows that the hottest fuel cladding temperature does not cause a nucleate boiling. During LOFA, the residual heat was removed by natural circulation flow that occurred slowly. In order to have larger inertia force, provision of the flywheel in the shaft of primary coolant pump is suggested.